Potensi dan Kontribusi UMKM Dalam Pengembangan Ekonomi Masyarakat Di Kelurahan Mudunglaut Kecamatan Pelayangan Kota Jambi - Siti Helmiati; Arsa; Hareastoma (CV. ALIM'SPUBLISHING, 2023)
The economic development of an area can have a positive impact within a certain period of time, in which a certain area that Micro, Small and Medium Enterprises (MSMEs) will affect the people's economy. Indonesia, which is a developing country, is not immune from problems that are commonly encountered in general, namely regarding how to manage the large number of human resources, the majority of whom are untrained and work productivity is still low. In Micro, Small and Medium Enterprises (UMKM) in Mudunglaut Village, Serpong District, it is a form of resource that has potential that needs to be developed optimally, which still has limited access for Micro, Small and Medium Enterprises (MSMEs) to productive resources, and is still weak. government facilitation in the introduction of MSME products in the form of promotions, provision of market space and information technology. The purpose of this study is to determine the potential and contribution of SMEs in the development of the community's economy from an Islamic economic perspective. This type of research uses qualitative methods, by observing, interviewing and documenting. Based on the results of this study, it was concluded that MSMEs in Mudunglaut Village have the potential to continue to grow, provided by the local government through the MSME business training program, so that businesses can be managed and developed properly. In the process of business activities carried out by MSME business actors it leads to the principles of Islamic provisions based on honesty in raw materials and the quality of products marketed